Influence of Traditional Indonesian Values and Local Culture on Teaching Practices and Student Engagement: A Comparative Study of Rural and Urban Schools - Rahmiwati; Dwi Sulisworo; Dody Hartanto (The Indonesian Institute of Science and Technology Research, 2026)
A school culture that supports collaboration, inclusivity, and openness to change can increase student engagement, teaching effectiveness, and academic achievement. Conversely, a more rigid or non-change-supporting culture tends to limit teachers' ability to implement learning innovations. The purpose of this study is to review recent research that highlights the influence of local cultural values ​​on teaching practices and student engagement in school. This research has gone through a process of identification, screening, eligibility, and inclusion through journals obtained from ERIC, Springer, and ScienceDirect. In reporting this research, the keywords used are